(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article articulates socially and politically-implied analyzes of the curatorial and healing processes that took place during the DESMONTE artistic-academic event held at the UFBA Dance School in two editions, 2019 and 2020. The main agenda of this event is to reflect on gender, race, sexuality, and disability using corporeal and intersectional perspectives. With the contribution of Trans Studies, Anti-colonial Studies and Anthropological Studies of the Anthropocene, three elements (the flame, the milk, and the table) of the performance (B)urra demanda de amor by Pérola Preta are assembled to compose arguments that signal clues from a cartography about wounds, the End of the World, witchcraft, healing, the creation of other worlds, and ways of being.